2014
DOI: 10.1016/j.jadohealth.2014.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Health Impact of Intimate Partner Violence and Non-partner Sexual Violence Among Female Adolescents Aged 15–19 Years in Vulnerable Urban Environments: A Multi-Country Study

Abstract: Significant heterogeneity was observed in the prevalence of IPV and non-partner sexual violence among adolescent women in economically distressed urban settings, with upwards of 25% of ever-partnered women experiencing past-year IPV in Baltimore, Ibadan, and Johannesburg, and more than 10% of adolescent women in Baltimore and Johannesburg reporting non-partner sexual violence. Findings affirm the negative health influence of GBV even in disadvantaged urban settings that present a range of competing health thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
156
2
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 45 publications
6
156
2
17
Order By: Relevance
“…[1- 3,11,14,15] The evidence linking demographic factors associated with IPV, including lower SES, the death of a father, and school factors such as repeating a school year and lower scores on school climate-related measures, suggests the need for proportionate universal multilevel models of intervention. Finally, more attention should be given to addressing community-level factors that can potentially protect young people from physical and sexual IPV perpetration and victimisation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[1- 3,11,14,15] The evidence linking demographic factors associated with IPV, including lower SES, the death of a father, and school factors such as repeating a school year and lower scores on school climate-related measures, suggests the need for proportionate universal multilevel models of intervention. Finally, more attention should be given to addressing community-level factors that can potentially protect young people from physical and sexual IPV perpetration and victimisation.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the prevalence of IPV in our study does correspond with that from studies with similar populations. [8,[11][12][13] Secondly, our study did not explore the characteristics of perpetrating partners who may be older or younger, or of the same or different sex. Again this is important for the development of interventions that could assist young people to report the abuse, as previous studies have shown that help-seeking by young people engaged in IPV is virtually non-existent and over half seek help from friends only.…”
Section: Study Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Une littérature scientifique émergente indique que parmi les enfants et adolescents de niveau socioéconomique faible, l'asthme, les problèmes cardiorespiratoires et les infections non transmises sexuellement sont plus fréquents chez ceux qui ont été maltraités en comparaison de ceux qui ne l'ont pas été ; ces problèmes entraîneraient plus d'hospitalisations et de plaintes somatiques (Lanier, Jonson-Reid, Stahlschmidt, Drake et Constantino, 2010 ;Rogosch, Dackis et Cicchetti, 2011). On observe également que les adolescentes exposées à la violence dans leurs relations amoureuses et à la violence sexuelle sont jusqu'à six fois plus à risque de rapporter une mauvaise santé générale que celles qui n'ont pas été exposées (Decker et al, 2014). Des adolescentes impliquées dans le système de justice présen-tant une exposition accrue à la violence familiale, l'agression physique et sexuelle durant l'enfance, présentent également plus de problèmes de santé physique généraux, de blessures, d'automutilation et d'hospitalisations que celles qui ont été moins exposées (Odgers, Robins et Russell, 2010).…”
Section: Santé Physique Chez Les Jeunes Agressés Sexuellementunclassified